ANALISIS PENGARUH VARIABEL MAKROEKONOMI TERHADAP JAKARTA ISLAMIC INDEX (JII) (PERIODE 2011-2022) - Raffy, Muhammad Raffy Nugraha; Iswan Noor (Islamic Economics and finance in Focus, 2024)
This research aims to analyze the influence of macroeconomic variables on the movement of the Jakarta Islamic Index (JII) during the period 2011-2022. The considered macroeconomic variables encompass economic growth, inflation, interest rates, exchange rates, and the Composite Stock Price Index (IHSG). The analytical method employed is regression analysis, complemented by classical assumption tests. The research findings indicate that inflation, interest rates, and IHSG significantly influence the movement of JII, while economic growth and exchange rates do not exhibit significant effects. The implications of these findings underscore the importance of considering macroeconomic factors in making investment decisions within the Sharia-compliant capital market, particularly concerning JII. However, it is essential to acknowledge certain limitations in this study, such as data constraints and generalization limitations. Therefore, the results should be interpreted cautiously, taking into account other potential factors that may impact the movement of JII.